Análisis del contenido del programa radio periódico actualidad de Radio Fluminense y su incidencia en la ciudadanía del cantón Babahoyo - Cevallos Cedeño, Olivia Marena (2020)
The present case study was carried out with the objective of analyzing the content of the Radio Periódico Actualidad program and its impact on the citizenship of Babahoyo, in order to publicize the structure that manages this news program in charge of recording current news, conducting interviews live, reports, and on the effect that this listener has on this program stands out more in the news of social help, and in guiding and educating the Riosense citizenship. The Radio Periódico Actualidad program is run by two broadcasters, Bolívar Moyano and Franklin Mero who have a degree in Social Communication, have been in charge of this program for approximately six years, where their main commitment is always to keep the inhabitants of the province informed. from the rivers. The techniques that were handled in this investigation were through an interview with Mr. Bolívar Moyano who has three years in the locution of the Radio Periódico Actualidad program, also conducted surveys of the citizens of the Babahoyo canton, and was raised as an observation in the listening the programming, so this released key information for the topic of interest. Throughout this investigation, the information published by the Radio Periódico Actualidad program broadcast by the radio station fluminense fm, which is located in the canton of Babahoyo and the favorable impact caused by this news program, is therefore shown. one of the highest, since this radial zone is widely heard throughout the province of Los Ríos.